MANAGEMENT OF HUMAN CAPITAL TRANSFORMATION IN UKRAINE IN WAR CONDITIONS - SHELEST, Oleksii; OBYDIENNOVA, Tetiana; DEMIANENKO, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Russia's war against Ukraine has caused serious social risks and significant losses of human capital, which create critical challenges for the development of the state. The reduction in the number and working capacity of the population, forced migration and the destruction of educational and scientific infrastructure lead to significant imbalances in the socio-economic system. In the process of military and post-war reconstruction, effective management of the transformation of human capital becomes a determining factor for maintaining Ukraine's competitiveness. The use of innovative approaches, strategic planning and anti-crisis management solutions allows minimizing losses and creating new opportunities for the modernization of educational, economic and social spheres, and also combines scientific novelty with practical value for the economy and public administration.The military aggression against Ukraine has caused significant socio-economic changes that directly affected the state and development of human capital. Mass migrations, demographic losses, and deterioration of the health and educational opportunities of the population have created critical risks for the preservation of the state's labor potential. The destruction of the labor market and educational and scientific infrastructure emphasizes the need for new management models for the effective transformation of human capital in the post-war period. Scientific study of the mechanisms for managing this transformation is of great theoretical and practical importance for strategic, innovative, and anti-crisis management.The purpose of the article is to theoretically substantiate and develop managerial approaches to the transformation of human capital in Ukraine in wartime, which involves identifying social risks, determining effective anti-crisis strategies, and substantiating innovative mechanisms for its restoration and further development.The study confirms that the transformation of human capital in wartime is a complex process that combines managerial, social and technological solutions. Effective management involves the simultaneous implementation of anti-crisis strategies and innovative approaches to the development of professional, social and psychological resources of the population. Recovery is based on the integration of state, corporate and educational initiatives that ensure flexibility, adaptability and sustainable development of human potential. The practical implementation of these approaches involves the analysis of the digital maturity of the enterprise, the assessment of internal resources and potential, as well as the development of strategic scenarios taking into account digital trends.
Keywords: human capital; transformation management; social risks; anti-crisis strategies; innovative approaches; restoration of human potential; war in Ukraine; digitalization of personnel management; socio-economic stability